Clinical Profile of Kerosene Poisoning in a Tertiary Level Hospital in Bangladesh - Anwar, S; Rahman, AKMN; Houqe, SK A; Moshed, AKMA; Yasmin, L; Saleh, ASM; Mohsin, M (Bangladesh Journal of Child Health, 2014)
Background: Accidental ingestion of kerosene continues to remain a common medical emergency among children in developing countries. The importance of this poisoning makes it imperative that parents should be aware about this poisoning. Objective: To see clinical profile of Kerosene poisoning in Bangladesh. Methodology: This retrospective study analyzed 56 children with acute kerosene poisoning admitted in Dhaka Medical College Hospital from January 2010 to June 2010 Result: Fifty six kerosene poisoning cases were admitted within 6 months period. Among the cases boys 29(51.8%), aged less than three years 52(93%), from a rural background 36(64%) and belonging to lower economic class 51 (91%) were found. Inappropriate container of kerosene like soft drink bottle 40 (71%) & summer season 40 (71%) were found major risk factor for kerosene ingestion. Cough 52 (92%) and dyspnea 51(91%) were the commonest clinical findings. Conclusion: Respiratory complaints are predominant clinical features of Kerosene poisoning. Toddler age, children from rural area, summer season were found major risk factors for kerosene ingestion and is mostly due to faulty packing & storage of kerosene. DOI: http://dx.doi.org/10.3329/bjch.v38i1.20021 Bangladesh J Child Health 2014; VOL 38 (1) : 11-14